German financial state aid during COVID-19 pandemic: Higher impact among digitalized self-employed - Irene Bertschek; Jörn Block; Alexander Kritikos; Caroline Stiel (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
In response to strong revenue and income losses that a large share of the self-employed faced during the COVID-19 pandemic, the German federal government introduced a exteuro50bn emergency aid program. Based on real-time online-survey data comprising more than 20,000 observations, we analyze the impact of this program on the subjective survival probability. In particular, we investigate how the digitalization level of the self-employed influences the program's effectiveness. Employing propensity score matching, we find that the emergency aid program had only moderately positive effects on the confidence of the self-employed to survive the crisis. However, the self-employed whose businesses were highly digitalized, benefitted much more from the state aid compared to those whose businesses were less digitalized. This holds true only for those self-employed in advanced digitalization stages, who started the digitalization processes already before the crisis. Moreover, taking a regional perspective, we find suggestive evidence that the quality of the regional broadband infrastructure matters in the sense that it increases the effectiveness of the emergency aid program. Our findings show the interplay between governmental support programs, the digitalization levels of entrepreneurs, and the regional digital infrastructure. The study helps public policy to increase the impact of crisis-related policy instruments.
Keywords: C14; H43; L25; L26; J68; O33; 330; Self-Employment; Emergency Aid; Treatment Effects; COVID-19; Entrepreneurship; Digitalization; Resilience